PENGARUH IMPLEMENTASI MANAJEMEN PESERTA DIDIK TERHADAP PRESTASI BELAJAR - Imas Aam Rahmawati (Jurnal Tata Kelola Pendidikan, 2021)
The aims of this study is about to know the effect of implementatiton student management on learning achievement at SMA Negeri 14 Kota Bandung. The study uses quantitative approach with descriptive methods. The population and sample in this study were 40 respondents who were teachers at SMA Negeri 14 Kota Bandung with a questionnaire and documentation research instrument. Processing data in this study used stastical applications SPSS 24.0 for windows and Microsoft Excel. The result of this study indicate that the effect of implementation student management on learning achievement at SMA Negeri 14 Kota Bandung has very low correlation, namely 0.132 and the correlation coefficient is 0.820 0,320 which means that the implementation of student management has no significant effect on learning achievement in SMA Negeri 14 Kota Bandung.